2021
DOI: 10.1111/bcp.14830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on the function of distal organs and oxidative stress after lower limb ischaemia–reperfusion in elderly patients undergoing unilateral knee arthroplasty

Abstract: This study aims to evaluate the effects of dexmedetomidine on organ function, inflammation response, and oxidative stress in elderly patients following iatrogenic lower limb ischaemia-reperfusion (IR) during unilateral total knee arthroplasty.Methods: Following unilateral total knee arthroplasty, 54 elderly patients were randomized to receive either intraoperative intravenous injection of dexmedetomidine (n = 27) or equivalent volume of 0.9% saline (n = 27). Blood samples were harvested at 5 minutes before low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Dexmedetomidine (DEX) is an e cient and intensely optional α2-adrenergic receptor agonist and functions as a polyfunctional medication in healing numerous human sicknesses [12]. As reported previously, DEX e ectively treats neural disorders by diminishing central nervous sympathetic efflux and offering calm and analgesia [13].…”
Section: Introductionmentioning
confidence: 95%
“…Dexmedetomidine (DEX) is an e cient and intensely optional α2-adrenergic receptor agonist and functions as a polyfunctional medication in healing numerous human sicknesses [12]. As reported previously, DEX e ectively treats neural disorders by diminishing central nervous sympathetic efflux and offering calm and analgesia [13].…”
Section: Introductionmentioning
confidence: 95%
“…24 Dex administration was associated with lower IL-6 levels 1 hr after surgery than the placebo group, suggesting that Dex mitigates against surgery-associated inflammation and potentially reduces the incidence of systemic inflammatory response syndrome. Preclinically, Dex has exhibited an inhibitory effect on inflammation, protecting both renal and pulmonary function, which may be through the activation of the PI3K/Akt signalling pathway via α 2 AR 11,15 and inhibition of the cholinergic anti-inflammatory pathway. 13 In addition, we did not find any difference in corticosteroid (Cor), catecholamine (CA) and acetylcholine (Ach) levels between the two groups, even though Dex is known to inhibit norepinephrine release and promote acetylcholine release.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous randomized controlled trial reported that Dex administration alleviated lung dysfunction induced by lower limb extremity ischemia-reperfusion. 15 These findings suggest that Dex may potentially reduce the incidence of postoperative renal and pulmonary dysfunction, thereby enhancing patient surgical outcomes. This study, therefore, is investigating whether Dex exhibits anti-inflammatory effects and further protects pulmonary and renal function in elderly patients undergoing prolonged major hepatobiliary and pancreatic surgery.…”
Section: Introductionmentioning
confidence: 97%